Análise de rotulagem de alimentos a partir da determinação, em larga escala, de gorduras trans - Ana Luisa Daibert Pinto (2016)
In this work a verification was made to show how TRANS fat is identified in food and nutrition information labels of processed products, especially those which state that "does not contain TRANS fat". In this study 251 food samples were analyzed regarding its content of total fat, TRANS fatty acids, saturated, monounsaturated and polyunsaturated fatty acids. These products are widely consumed by the population, especially those which claim to be "zero TRANS". It was verified if the labeling was in accordance with the legislation and the results were compared with the data stated on the labels of the samples. According to the RDC Resolution 360/2003 of ANVISA, the disclosure of TRANS fatty acids content on the food label is mandatory when the levels are greater than 0.2 g in the food portion. Products containing less than 2 g/ per portion can be reported on the label as "zero TRANS." The aim of this study was to evaluate the amount of saturated and TRANS fat in many groups of processed food and its adequacy towards the Brazilian law, especially regarding their disclosure on the product label.. For the analysis, the official method of fat analysis AOAC 996.01 (modified) and the methyl esters of fatty acids AOAC 996.06 were used. According to the results obtained, some products in 100g, exceeded the amount of 2g/day which is recommended in several countries regarding the total daily intake of TRANS fatty acids. Many products were in compliance with the law (TRANS fat 0.2 g per serving), which does not necessarily imply a zero TRANS fat content, giving the false impression to the consumer of not being ingesting any TRANS fat regardless of the amount consumed. Only 12 samples really showed 0g of TRANS fat (100g of product). It should also be noticed that many times the amount of food consumed is higher than the suggested serving, resulting in a significant intake of TRANS fatty acids. The results presented herein provide enough evidence for further reflection on possible changes in current legislation, requiring the content of TRANS fatty acids on the label, regardless of the quantity contained in the portion, a standardization of quantity in each portion and the need for a periodicity of nutritional analysis of industrialized products.